When every hour counts: reasons for delay in rabies post-exposure prophylaxis in a tertiary healthcare center in central India - Kumar, Mohit; Jain, Mudita; Kannan, Surya; Bansod, Teresa; Narlawar, Uday (International Journal Of Community Medicine And Public Health, 2025)
Background: Timely initiation and completion of post-exposure prophylaxis (PEP) following animal bite is critical to prevent rabies, a uniformly fatal but vaccine-preventable disease. Despite availability of effective vaccines, delays in initiation and administration of PEP are frequently reported in India. Objective was to describe the various reasons for delay in initiation and administration of PEP following animal bite. Methods: A hospital based cross-sectional study was conducted among animal bite victims attending the anti-rabies clinic of GMC Nagpur from 10th June to 10th September 2024. Data were collected using a pre-tested structured questionnaire on socio-demographic profile, characteristics of the bite, and reasons for delay in seeking or receiving PEP. Descriptive statistics were used to summarize findings. Results: A total of 184 animal bite cases were enrolled, of whom 86% experienced delay in initiation of PEP. Socio-economic distribution showed that more than two-thirds of participants belonged to the middle and lower-middle classes (69.6%), with very few from upper strata (1.1%). Dogs were the predominant biting animal (90.2%) with most common bite sites being hands (35.9%) and legs (25.5%). Major reasons reported for delay included referral to other health centers (22.8%), facility closed (17.9%) and non-availability of vaccine at local health facilities (16.3%). Conclusions: Multiple individual, social, and system-related barriers contribute to delay in initiation and administration of PEP. Strengthening awareness campaigns, improving accessibility and uninterrupted availability of vaccines, and community-level counselling are essential to ensure timely prophylaxis and prevent rabies deaths.